(3TQM bUjOI efShHI dYdj Hf CHj WGdHs - (3hdj Hf eMeO GdNWjHs
(3ChdgG (B:s
(3GdMeO ddg (B... (3hdG GNHQYdjg HMHSg hMHShg YfO egJQ HGTj Edi KGfj jhe hCeQ Ydjg Gf jVQHhg hVQHhg KdGK eGFI YUG HGdNRfI Ke HYO CeQ Gf jMHShg (B...s
(3BNQgG (B:s
.. (3bhdg JYGdi aChdFc GdPjf gOi Gddg aHgOGge GbJOg cj JgJOj HgOGjJj GdJj gOGfj Gddg EdjgG hGdSdGe Ydi ef GJHY GdgOjs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdCOHs